2009
DOI: 10.1124/mol.108.053462
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Morphine Treatment Decreases the Association of μ-Opioid Receptor (MOR1) mRNA with Polysomes through miRNA23b

Abstract: ABSTRACT-Opioid receptor (MOR) mediates most of the pharmacological effects of opioid drugs. The expression of MOR is temporarily and spatially regulated at both the transcriptional and post-transcriptional levels. Long-term morphine treatment that induces tolerance does not alter MOR mRNA expression, suggesting no direct link between agonist treatment and MOR gene transcription. We previously identified the 3Ј-untranslated region (3Ј-UTR) of the major transcript of -opioid receptor (MOR1) and revealed a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 33 publications
2
76
0
Order By: Relevance
“…Increasing evidence suggests that morphine treatment can modulate the expression of various miRNAs (Wu et al 2009;Dave and Khalili 2010;Sanchez-Simon et al 2010). Since morphine down regulates the expression of anti-HIV miRNAs in monocytes in vitro and heroin addicts have lower levels of these miRNAs in PBMCs (Wang et al 2011), and down-regulation of these miRNAs can promote replication of latent HIV-1 in resting CD4+ T cells (Huang et al 2007) and in monocytes (Wang et al 2009) …”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that morphine treatment can modulate the expression of various miRNAs (Wu et al 2009;Dave and Khalili 2010;Sanchez-Simon et al 2010). Since morphine down regulates the expression of anti-HIV miRNAs in monocytes in vitro and heroin addicts have lower levels of these miRNAs in PBMCs (Wang et al 2011), and down-regulation of these miRNAs can promote replication of latent HIV-1 in resting CD4+ T cells (Huang et al 2007) and in monocytes (Wang et al 2009) …”
Section: Discussionmentioning
confidence: 99%
“…We further illustrated that miR-103/107 mainly functions at the post-transcriptional or translational level to regulate MOR-1A expression, as shown by the increase in polyribosomeassociated MOR-1A mRNA when the mutant construct and miR-107 inhibitor were used, without affecting steady-state mRNA levels. Previous studies indicated that several miRNAs such as miR-23b and let-7 inhibit the expression of the original mMOR-1 at the post-transcriptional level through their binding sites located at the 39-UTR (Wu et al, 2008(Wu et al, , 2009He et al, 2010). Our study shows for the first time that a pair of paralogous miRNAs, miR-103 and miR-107, can regulate the expression of a C-terminal splice variant at the post-transcriptional level through its 39-UTR, as determined by measurement of polyribosome-associated mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Mu opioids such as morphine modulate expression of a number of miRNAs (Sanchez-Simon et al, 2010;Zheng et al, 2010;Wu et al, 2008Wu et al, , 2013Dave and Khalili, 2010;He et al, 2010;Wang et al, 2011), and several miRNAs regulate MOR-1 expression (Wu et al, 2008(Wu et al, , 2009He et al, 2010). Dysregulation of miRNAs has been linked to morphine tolerance and addiction Dreyer, 2010;Hwang et al, 2012;Tapocik et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings demonstrated miRNAs as significant modulators in controlling the impacts of abused drugs such as cocaine, nicotine, morphine and opioids, on brain rewarding circuits and the development of addiction-related behaviors678910. LncRNAs are known to control genes expression through various mechanisms and are likely to influence brain development, neuronal plasticity, and neural disease1112131415.…”
mentioning
confidence: 99%